Enzymatic deacidification of alpha-linolenic acid -enriched oils with negligible change in triacylglycerol composition. (December 2021) - Xu, Qingqing; Lan, Dongming; Liu, Xuan; Yang, Bo; Sun-Waterhouse, Dongxiao; Liao, Sentai; Wang, Weifei; Wang, Yonghua
Graphical abstract: Highlights: Deacidification system for alpha-linolenic acid -enriched oils was established. Lipase G was first applied in deacidification. The triacylglycerol (TAG) content and TAG profile showed no change. Phosphatidylcholine and phosphatidylethanolamine were highly retained. Abstract: In recognition of the demand for fit-for-purpose oil deacidification processes, an industrially feasible enzymatic deacidification system was established for alpha-linolenic acid (ALA)-enriched oils using Lipase G (from Penicillium camembertii ) immobilized with ECR8806 resins. The system was first built based on crude silkworm pupal oil (SPO). The advantages of this system include unchanged triacylglycerol composition and content (∼81 %) after deacidification, high reusability for immobilized Lipase G (unchanged deacidification efficiency (∼97 %) after 10 batches), and high retention of desired substances (retained tocopherol, sterol, phosphatidylcholine and phosphatidylethanolamine contents: 87.62 ± 2.29 %, 88.81 ± 2.06 %, 96.94 ± 1.43 % and 95.67 ± 1.09 % respectively). Minimal change was found in efficiency after scaling up the deacidification process (laboratory-scale: 97.03 ± 0.30 %; scale-up: 94.46 ± 0.38 %) under optimal conditions (crude SPO- n -hexane ratio, 1:4 ( w:v ); free fatty acid-ethanol molar ratio 1:2; enzyme loading, 45 U/g oil; 40 °C for 6 h). And this is the first report on a deacidification process that can preserve largely PC and PE contents in oil. The established deacidification system was further applied to crude flaxseed and perilla seed oil without the change of any conditions and showed good fitness for ALA-enriched oils.